ChemInform Abstract: Highly Enantioselective SPINOL‐Derived Phosphoric Acid Catalyzed Transfer Hydrogenation of Diverse C=N‐Containing Heterocycles. Issue 37 (September 2015) - Zhang, Yiliang; Zhao, Rong; Bao, Robert Li‐Yuan; Shi, Lei
Abstract Hydrogenation of C=N‐containing heterocycles is carried out by using 1, 1′‐spirobiindane‐7, 7′‐diol‐derived chiral phosphoric acids as the catalyst.